The role of P3H family in cancer: implications for prognosis, tumor microenvironment and drug sensitivity - Wang, Ziyun; Wang, Hua (Frontiers in Oncology, 2024)
This research aims to investigate the involvement of the P3H family, responsible for collagen proline 3-hydroxylation, in 33 different forms of cancer. Additionally, we sought to explore how this family influences the tumor microenvironment (TME), prognosis, and immune infiltration.The investigation involved a comprehensive analysis of expression profiles and clinical data obtained from the Genotype-Tissue Expression (GTEx) and The Cancer Genome Atlas (TCGA) databases. This included the assessment of genetic variation, gene expression, and the prognostic significance of P3H family genes. P3H scores were calculated using various databases and R-based tools, followed by correlation analyses with the TME, immune cell infiltration, drug sensitivity and immunotherapy .Variations in P3H gene expression patterns were observed across different tumor types and prognoses, suggesting that most genes within the family were risk factors, especially P3H1 and P3H4. The P3H score was associated with immune infiltration and drug resistance. Notably, individuals with elevated expression of P3H2, P3H3, and CRTAP exhibited higher resistance to multiple anti-tumor drugs.P3H family proteins play diverse roles in cancer progression, significantly impacting patient prognosis and the effectiveness of immunotherapy. The P3H score, identified as a potential biomarker for evaluating TME, holds promise in guiding precision medicine strategies. 1Introduction * 删除[王子赟 [2]]: